Illustrated keys for neotropical sphecids (Apoídea:Sphecidae) subfamilies, tribes, and genera - Menke, Arnold S. (1996)
141 genera of Sphecidae, representing 1,628 species, are known from the Neotropical Region. Illustrated keys to genera, tribes, and subfamilies are presented in Spanish and English. These have been modified and updated from those in Bohart & Menke's 1976 book, Sphecid Wasps of the World. The validity of a few genera recognized by Bohart & Menke is now in question and the keys are annotated to alert users to these problems. A list of neotropical genera and higher taxa is included. Names in the list are appended with significant literature published since 1976. The history and current status of subfamilies are reviewed. Ten subfamilies are recognized. Family characters and biology are summarized. Morphological terms are illustrated and a glossary provided.